Prevalence of dermatophytosis in cats at Alfa Animal Clinic Banda Aceh - Yuliansyah, Nanda; Zamzami, Rumi Sahara; Ferdian, Riyan; Daud, Razali; Hamzah, Abdullah (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Dermatophytosis, a significant health issue in cats, is a dermatological condition caused by dermatophyte fungi, primarily involving the genera Microsporum, Trichophyton, and Epidermophyton. This study investigates the prevalence of dermatophytosis in cats at Alfa Animal Clinic, Banda Aceh, from June to November 2023. The prevalence of dermatophytosis varies geographically, influenced by climate, environmental conditions, and owner awareness. This study found a prevalence rate of 1.040% with 51 cases among 490 cats. The research highlights the need for improved hygiene practices, regular veterinary check-ups, and education for pet owners to manage and prevent dermatophytosis. The findings underscore the importance of ongoing surveillance and targeted interventions to control this zoonotic infection, ensuring better health outcomes for the feline population.